Characteristics of Arabic Chicken (Gallus turcicus) Egg Flour with Different Drying Methods - Angga Maulana Firmansyah; Nicolays Jambang; Lukman Hakim; Selma Noor Permadi; Teguh Wahyono; Laila Rahmawati; Ahmad Iskandar Setiyawan; Andi Febrisiantosa; Athiefah Fauziyyah (Jurnal Ilmu Pertanian Indonesia, 2026)
Eggs of Arabic chicken (Gallus turcicus) have a high nutritional value and distinct traits, although they have a short shelf-life (about 17 d) and are prone to contamination. To address this issue, drying methods such as oven-drying, spray-drying, and freeze-drying can be employed to convert eggs to flour. This study investigated the physicochemical and microbiological properties of Arab chicken egg flour produced using various drying procedures to give comparative data and aid in the development of novel egg-based products. The study found that different drying processes had substantial (p <0.05) effects on color (L*, a*, b*), moisture, ash, fat, and protein contents. The freeze-drying method produced the best results, including color with a brightness level (L) of 66.69, redness (a*) of 22.73, and yellowness (b*) of 51.23; moisture of 1.53%; ash content of 7.04%; fat of 36.94%; protein of 51.73%; and total microbial contamination of 1.2 × 102 cfu/g. The freeze-drying process fulfills the Indonesian National Standard (SNI) and the United Nations Economic Commission for Europe (UNECE) Standard, making it a useful reference for drying procedures that preserve the quality and shelf life of Arabic chicken eggs. Keywords: Arabic chicken, drying, egg powder, microbiology, physicochemistry